Production capacity of Broiler Chickens Given Dietary Red Guava Fruit Meal as source of Natural Antioxidant - Sian H. L. Bikrisima; L. D. Mahfudz; N. Suthama (Jurnal Ilmu dan Teknologi Peternakan, 2014)
The aim of the research was to determine the effectivity of the dietary inclusion of red guava fruit on the production capability of broiler chicken. An amount of 120 birds of unsex broiler chicken were randomly assigned in floor pen based on a completely randomized design (CRD) with 5 treatments and 4 replications consisted of 6 chicken each. Dietary treatments of the inclusion of red guava fruit were offered for 4 weeks, i.e.: without red guava (T0), 1.7% (T1), 3.4% (T2), and 5.1% (T3) respectively red guava fruit meal and diet with synthetic vitamin C (T4). The parameters measured were production capability (muscle protein and calcium mass, carcass weight, meat, and bone production). The results showed that muscle protein mass, calcium mass and bone production showed no significant differences (P>0.05) due to the treatments. Weight of carcass of T2 was significantly highest (617.75 g) compared to other treatments and meat production was significantly higher (259.25 g) compared to T4 (193.25 g), but not significant differences compared to other treatments. The results of the present study can be concluded that feeding red guava fruit meal at the level of 3.4% equal to 500 ppm vitamin C as a source of  natural antioxidant can improve production capability.